Environmental Sustainability in Selected OPEC Countries: Do the Influence of FDI and ICT Matter? - Hamid Sepehrdoust; Mohsen Tartar; Saber Zamani Shabkhaneh; Shaghayegh Heydari Parvin (SAGE Publishing, 2023)
Considering the undeniable role and importance of the environment in people's lives, the present study is designed to investigate the combined effect of information and communication technology (ICT) and foreign direct investment (FDI) on achieving environmental sustainability. Since the increasing emission of carbon in society and its destructive environmental effects on social economic aspects and even political tensions have become a challenge, the main question of the research is what strategies have governments, especially oil exporting countries, used in the past to reduce the level they have discovered pollution and what policies do they want to follow in the future? Among the policies undertaken by the OPEC oil exporting countries, has the action for foreign direct investment (FDI) and the development of information and communication technology (ICT) been effective in preventing harmful environmental effects? For this purpose, data on renewable energy consumption, the intensity of use of information and communication technology, foreign direct investment (FDI), and urbanization have been used as explanatory variables, and carbon dioxide (CO 2 ) emission as a dependent variable. The target countries selected are oil exporting countries (OPEC) for the period 2000 to 2020, and the analysis method used is panel VAR. The results showed that creating a shock in FDI, labor force, urban population, and renewable energy consumption decreases CO 2 while creating a shock in Gross capital formation increases CO 2 . The impact of shock of ICT on CO 2 is also insignificant and can be ignored. The results of variance analysis also showed that urban population, labor force, and FDI variables have the largest contribution in explaining the behavior of CO 2 ; therefore, it is necessary to pay attention to FDI and try to increase the attraction of foreign direct investment to reduce CO 2 in OPEC countries. JEL: C23, F43, F64